Cultivating words: integrating immersive technologies and translation in agricultural settings - Karasaliu, Alma; Palla, Ilir (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study explores an innovative pedagogical approach that integrates translation, educational technology, and virtual reality (VR) to enhance domain-specific language acquisition and digital engagement among undergraduate students in agricultural education. The 18 first-year students enrolled in “Agricultural Business Management” at Fan S. Noli University participated in a study combining immersive virtual experiences, translation tasks, and artificial intelligence (AI) tools. Students used platforms like Google Earth VR and 360Cities to describe agricultural environments in Albanian, and translated these texts into English using human and machine translation (Google Translate). The translated texts were then visualized through DALL·E to stimulate reflection on the semantic representation of the original scenes. Mozilla Hubs supported collaborative analysis of translation quality and peer feedback. Statistical analysis using R software (version 4.3.1) included the Welch two-sample t-test and Wilcoxon signed-rank test to compare translation outcomes. The results indicated significant improvement in technical vocabulary retention and increased students’ awareness of translation complexities. Moreover, students reported heightened motivation and positive attitudes toward technology-enhanced language learning. The study highlights the pedagogical value of immersive, interdisciplinary strategies in English for specific purposes (ESP), particularly in technical disciplines like agriculture.